SELF RESCUE SYSTEM IN DISASTERS USING SMARTPHONES - T.Sunitha, K.Naga Nandana Valli , Y.Sai Nagalakshmi, K.Pavithra, J.Venkata Jayanthi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Recent widespread earthquakes have caused widespread devastation of electrical power and cellular infrastructures, leaving millions of people without access to electricity and communication. As a result of the widespread earthquake tragedy, no electricity and The golden hours are lost due to ineffective and time-consuming rescue efforts and outdated equipment as well as a lack of a reliable communication system. It is reasonable to suppose that many catastrophe victims will have access to strong wireless devices like smartphones, which may be used to coordinate rescue efforts. In this study, we suggest the use of a smartphone-based self-rescue system called our system to aid in disaster relief and rescue efforts. Our system's central concept is that a group of cellphones belonging to survivors who are trapped or buried beneath the collapsed infrastructure establish a one-hop network and send out a distress signal in an energy-efficient way to surrounding rescue workers. We conduct a comprehensive simulation experiment to assess the suggested method and compare its results to those of the already established teamphone system. The simulation findings suggest that the suggested method may be a realistic way to speed up disaster rescue and relief activities by drastically decreasing the schedule vacancy of broadcasting distress signals and increasing the detection probability with little impact on network lifespan.